Augmented Reality on Android for Identifying and Learning about Orchids - Heningtyas, Yunda; Hadad, Azizal; Wulansari, Ossy Dwi Endah (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2024)
Indonesia, as an agricultural country, has a wealth of various plants which are often used as ornamental plants because of their beauty, including the popular orchids. The diversity of orchids offers various opportunities for development, both for cut flowers and decoration. However, orchids are sensitive plants, requiring special care depending on the type, including growing media, water requirements, and proper temperature. Therefore, accurate information is very important for orchid fans. To answer this need, an Android-based application that utilizes Augmented Reality technology has been developed to make the delivery of information about orchid plants more interactive. Augmented Reality is a technology that combines 2D or 3D virtual objects with the real three-dimensional world, which then displays these virtual objects in real-time. With this technology, users can see 3D representations of orchids and get information through integrated video. The Multimedia Development Life Cycle method was used in developing this application, which aims to make it easier for users to understand various types of orchids and how to care for them. The Information Orchid Type Application (IJA) allows users to zoom and rotate 3D virtual objects of five types of orchid plants.